2016
DOI: 10.1038/onc.2016.282
|View full text |Cite
|
Sign up to set email alerts
|

The novel G-quadruplex-containing long non-coding RNA GSEC antagonizes DHX36 and modulates colon cancer cell migration

Abstract: Long non-coding RNAs (lncRNAs) are frequently dysregulated in a variety of human cancers. However, their biological roles in these cancers remain incompletely understood. In this study, we analyze the gene expression profiles of colon cancer tissues and identify a previously unannotated lncRNA, FLJ39051, that we term GSEC (G-quadruplex-forming sequence containing lncRNA), as a lncRNA that is upregulated in colorectal cancer. We further demonstrate that knockdown of GSEC results in the reduction of colon cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 43 publications
1
65
0
Order By: Relevance
“…In addition, previous studies have shown that DHX9 plays an important role in maintaining gene stability and promotes the survival of tumor cells [44] [45] [46]. Recent proteomic studies also suggest elevated DHX9 expression levels in CRC, whereas DHX36 silence reduced CRC invasiveness and metastasis [26] [47]. These studies indicate that the helicase family may be also involved in the development of CRC.…”
Section: The Expression Profile Of Helicases Family Members In Crcmentioning
confidence: 88%
“…In addition, previous studies have shown that DHX9 plays an important role in maintaining gene stability and promotes the survival of tumor cells [44] [45] [46]. Recent proteomic studies also suggest elevated DHX9 expression levels in CRC, whereas DHX36 silence reduced CRC invasiveness and metastasis [26] [47]. These studies indicate that the helicase family may be also involved in the development of CRC.…”
Section: The Expression Profile Of Helicases Family Members In Crcmentioning
confidence: 88%
“…Recent work from Matsumura et al . demonstrated the biological relevance of a G4 in the lncRNA GSEC (G-quadruplex-forming sequence containing lncRNA) 167 . This cytoplasmic lncRNA is implicated in the development of colorectal cancer where it stimulates migration of colon cancer cells, and depletion of GSEC results in the reduction of cancer cell mobility.…”
Section: Emerging Roles Of Rna G4s In Biology Of Non-coding Rnasmentioning
confidence: 99%
“…DHX36 recognizes a G4 in GSEC , and mutations of key guanines that affect G4 folding also reduce their interaction. Functionally, DHX36 inhibits mobility of colon cancer cells and GSEC antagonizes its effect by acting as a molecular decoy to suppress DHX36 function 167 .…”
Section: Emerging Roles Of Rna G4s In Biology Of Non-coding Rnasmentioning
confidence: 99%
“…as in long-noncoding RNA (Matsumura et al 2017), suggesting roles of rG4 in the noncoding RNA transcriptome. Herein, we describe recent methodological advances to detect rG4s in the transcriptome.…”
Section: Introductionmentioning
confidence: 99%